Uveitis output in high-impact clinical ophthalmology journals: a bibliometric analysis - Baotram V. Nguyen; Priyanka Bhatnagar; Daniel C. Lee; Meghan K. Berkenstock (Journal of Ophthalmic Inflammation and Infection)
Abstract Background Despite uveitis subspecialty workforce shortages, uveitis specialists remain engaged in research. This study examines the relationship between the proportions of uveitis-focused articles in high-impact ophthalmology journals and fellowship-trained uveitis specialists on their editorial boards. Methods A bibliometric analysis was conducted on articles published from 2014 to 2023 in the five highest-impact ophthalmology journals: Ophthalmology, JAMA Ophthalmology, British Journal of Ophthalmology (BJO), American Journal of Ophthalmology (AJO), and Investigative Ophthalmology and Visual Science (IOVS). Editorial board members with uveitis or ocular immunology fellowships were identified from public domain sources. Articles were screened using uveitis MeSH terms. Data analysis was performed using STATA to assess the relationship between the proportions of uveitis-focused articles and uveitis-trained editors. Results From 2014 to 2023, 3.57% (575/16,093) of articles published in the five journals were uveitis-focused. The proportion of uveitis-focused articles ranged from 1.74% in IOVS to 5.89% in AJO. On average, fellowship-trained uveitis specialists comprised 5.28% of editorial board members annually. There were positive correlations between the proportions of uveitis-focused articles and uveitis-trained editors annually (r = 0.6799, p < 0.00005) and over the 10-year period (r = 0.2675, p < 0.00005). No significant correlation was observed within individual journals. Conclusions Uveitis research remains underrepresented in high-impact ophthalmology journals despite research productivity in the field. While a positive correlation between uveitis-trained editors and uveitis-focused articles was found across all journals, this trend did not hold within individual journals. Enhancing uveitis research visibility in high-impact journals is essential to advancing clinical knowledge, improving patient outcomes, and inspiring ophthalmologists to enter this underserved subspecialty.